2015
DOI: 10.5539/jas.v7n6p84
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Dough and Quality of Salted Noodles Supplemented with Djulis (Chenopodium formosanum Koidz.) Flour

Abstract: Djulis (Chenopodium formosanum Koidz.) has attracted attention worldwide for its nutritional value and health benefit. To examine the potential application of djulis flour in oriental starch-based staple products, we supplemented wheat flour with djulis flour in different proportions to investigate the rheological properties of dough and determine the sensory and textural profile of salted noodles. For dough characteristics measured by farinography and extensography, increased amount of djulis flour decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The increase of water absorption could be explained by the important number of hydroxyl groups existing in the fiber structure, which allow more water interactions through hydrogen bonding 5.9 ±0.0* 6.6 ±0.1* 211.2 ±8.2* 6.9 ±0.0* Note: PPpumpkin powder, OCToptimal cooking time, PWApasta water absorption, * denotes statisticaly significan difference at p -0.05 level. CL is defined as the amount of solids that dissolve in water during cooking and may be an indicator of noodle structural integrity during cooking (Li et al, 2015). As a result, the cooking water becomes cloudy and thick (Ajila et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The increase of water absorption could be explained by the important number of hydroxyl groups existing in the fiber structure, which allow more water interactions through hydrogen bonding 5.9 ±0.0* 6.6 ±0.1* 211.2 ±8.2* 6.9 ±0.0* Note: PPpumpkin powder, OCToptimal cooking time, PWApasta water absorption, * denotes statisticaly significan difference at p -0.05 level. CL is defined as the amount of solids that dissolve in water during cooking and may be an indicator of noodle structural integrity during cooking (Li et al, 2015). As a result, the cooking water becomes cloudy and thick (Ajila et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…CWA indicates the amount of water absorbed by the pasta during cooking [31]. According to the MSZ 20500/1-1985 standard, CWA must be at least 100% of the dry pasta mass.…”
Section: Cooking Properties Of Pastamentioning
confidence: 99%
“…Cooking loss is amount of solids that dissolve in water during cooking and may be an indicator of noodles structure integrity during cooking Li et al, (2015). Cooking loss is commonly used as predictor of overall noodle cooking performance Tudorica et al, (2002).…”
Section: Cooking Lossmentioning
confidence: 99%
“…Water absorption is indication of quantity of water absorbed by the noodles during cooking, an important characteristics in deciding the cooking quality Li et al, (2015). Results indicated that, there was slight increase in water absorption and consequently in cooking weight of noodles.…”
Section: Water Absorptionmentioning
confidence: 99%